Preparation of Alginate/Lignosulfonat as Shell Materials For Neem Oil Encapsulation - Dea putri Ismawardani; Dwi Indarti; Bambang Piluharto (Department of Chemistry, FMIPA, UNEJ, 2025)
Azadirahtin is one of the active ingredients in neem oil which acts as an antifeedant and repellant for several types of insects so it is widely used as a pesticide. However, Azadirahtin has a weakness that is susceptible to light which is easy to degrade. The purpose of this study was to encapsulate azadirahtin in neem oil in a lignosulfonate/alginate matrix. Here there are two types of lignosulfonate (LS): LS from technical materials and LS from pure analysis (PA) (higher purity level). The preparation of the alginate matrix was carried out through the ionic gelation method. Characterization of the beads obtained included the degree of swelling carried out using the gravimetric method, the structure using FTIR and the stability of photodegradation using the UV-VIS spectrophotometry method. The results obtained showed that physically the beads had a hydrogel texture with a brownish yellow color. The swelling behavior of the beads showed differences in the degree of swelling pattern of beads with the addition of technical LS and LS Pure analysis (PA). The addition of LS PA Increasing the soaking time increases the degree of swelling, while beads with the addition of Technical LS produce fluctuating degree of swelling. Meanwhile, the results of the photodegradation stability test, a shorter distance between the UV light source and the object shows a higher photodegradation rate